Solar-irradiated carbon dots as high-density hot spots in sponge for high-efficiency cleanup of viscous crude oil spill. Issue 2 (15th December 2021) - Su, Yucheng; Chang, Qing; Xue, Chaorui; Yang, Jinlong; Hu, Shengliang
Abstract : A novel solar-heating superhydrophobic sorbent system created by the in situ chemical reaction of carbon dots with commercial porous sponge has been developed for the high-speed sorption of viscous crude oil from a seawater surface. Abstract : A rational architecture of photothermal layers on the scaffold surface of porous sorbents is highly desirable for the targeted delivery of sustainable solar energy to power the oil spill remediation process, but its realization remains challenging. Here, we report a novel solar-heating superhydrophobic sorbent system that is created by the in situ chemical reaction of carbon dots (CDs) and commercial porous sponge (CPS), effectively reducing the viscosity of crude oil and speeding up the oil adsorption rate. The superior solar-to-heat conversion together with the excellent heat management endow our presented sorbent system with a crude oil absorption capacity of nearly 60 g g −1 within a very short time under one-sun irradiation, which is significantly faster than previously reported sorbents fabricated by dip-coating methods. This feature is mainly attributed to the decoration of homogeneous and high-density CDs on CPS. Given the fundamental design principle, low operating cost, and fast oil-recovery rate, this work provides possibilities for solar-powered large-area crude oil spill remediation.